Projected 20- and 30-Year Outcomes for Pediatric Liver Transplant Recipients in the United States. Issue 3 (March 2020) - Bowring, Mary G.; Massie, Allan B.; Chu, Nadia M.; Bae, Sunjae; Schwarz, Kathleen B.; Cameron, Andrew M.; Bridges, John F.P.; Segev, Dorry L.; Mogul, Douglas B.
ABSTRACT: Background: Observed long-term outcomes no longer reflect the survival trajectory facing pediatric liver transplant (LT) recipients today. We aimed to use national registry data and parametric models to project 20- and 30-year post-transplant outcomes for recently transplanted pediatric LT recipients. Methods: We conducted a retrospective cohort study of 13, 442 first-time pediatric (age <18) LT recipients using 1987 to 2018 Scientific Registry of Transplant Recipients data. We validated the proposed method (ie, to project long-term patient and graft survival using parametric survival models and short-term data) in 2 historic cohorts (1987–1996 and 1997–2006) and estimated long-term projections among patients transplanted between 2007 and 2018. Projections were stratified by raft type, recipient age, and indication for transplant. Results: Parsimonious parametric models with Weibull distribution can be applied to post-transplant data and used to project long-term outcomes for pediatric LT recipients beyond observed data. Projected 20-year patient survival for pediatric LT recipients transplanted in 2007 to 2018 was 84.0% (95% confidence interval 81.5–85.8), compared to observed 20-year survival of 72.8% and 63.6% among those transplanted in 1997 to 2006 and 1987 to 1996, respectively. Projected 30-year survival for pediatric LT recipients in 2007 to 2018 was 80.1% (75.2–82.7), compared to projected 30-year survival of 68.6% (66.1–70.9) in the 1997 to 2006 cohort and observed 30-year survival of 57.5% in the 1987 to 1996 cohort. Twenty- and 30-year patient and graft survival varied slightly by recipient age, graft type, and indication for transplant. Conclusions: Projected long-term outcomes for recently transplanted pediatric LT recipients are excellent, reflective of substantial improvements in medical care, and informative for physician-patient education and decision making in the current era. Abstract : Supplemental Digital Content is available in the text